A Selective Colorimetric and Fluorometric Chemosensor Based on Conjugated Polydiacetylenes for Cadmium Ion Detection. Issue 11 (20th September 2019) - Pham, Thanh Chung; Kim, Yong Kyun; Park, Jung Bin; Jeon, Sumin; Ahn, Juhyeon; Yim, Yubin; Yoon, Juyoung; Lee, Songyi
Abstract: In the current study, a polydiacetylene (PDA)‐based sensor, derived from a chelidamic acid‐picolylamine (CP)‐substituted diacetylene monomer, displayed a selective colorimetric and fluorometric change in the presence of cadmium (Cd 2+ ) at pH 7.4. The PDA−CP solutions showed a colorimetric change from blue to violet in response to various amounts of Cd 2+ . The chemosensor also showed a rapid fluorescence turn‐on response and significant selectivity to Cd 2+ compared with other metallic cations. The Cd 2+ ‐selective PDA‐based sensor system facilitated the visual detection of Cd 2+ in aqueous solution. The Cd 2+ detection limit of PDA−CP was reduced to 1.85×10 −5 M. Abstract : Makes sense ! A chelidamic acid‐picolylamine (CP) substituted diacetylene (PDA−CP) was prepared and employed as a colorimetric and fluorometric chemosensor for Cd 2+ ions. In this system, the CP chelating moieties serves as a recognition moiety for cadmium ions.